GAYA KEPEMIMPINAN, MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. DUA PUTRI CILIWUNG BANYUWANGI - Hasan Abdullah (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This studys aim to analyzze the influeence of leadershiip style and work motivatiion on employee performaance of PT Dua Putri Ciliwung Banyuwangi . The study population was all employees of PT Dua Putri Ciliwung Banyuwangi maany as 35 peoples . The method used in this study among others: test validity , reliability , Multiple Linear Regression Analysiis , Multiple coefficient of determination ( R2 ) , F test , t test , test and test Multicolinearity Heteroskidastity . The conclusion of this study is the variable of leadersship stylle and works motivation simultaneeously significantly influence employee performance , while partial leadership style also has a significant influence on the performance of employees of PT Dua Putri Ciliwung Banyuwangi